Clinical‐Pathologic Correlation Between Transperineal Mapping Biopsies of the Prostate and Three‐Dimensional Reconstruction of Prostatectomy Specimens. Issue 7 (20th November 2012) - Crawford, E. David; Rove, Kyle O.; Barqawi, Al B.; Maroni, Paul D.; Werahera, Priya N.; Baer, Craig A.; Koul, Hari K.; Rove, Cory A.; Lucia, M. Scott; La Rosa, Francisco G.
Abstract: BACKGROUND: Extended transrectal ultrasound guided biopsies (TRUSB) of the prostate may not accurately convey true morphometric information and Gleason score (GS) of prostate cancer (PCa) and the clinical use of template‐guided (5‐mm grid) transperineal mapping biopsies (TPMBs) remains controversial. METHODS: We correlated the clinical‐pathologic results of 1, 403 TPMB cores obtained from 25 men diagnosed with PCa with 64 cancer lesions found in their corresponding radical prostatectomy (RP) specimens. Special computer models of three‐dimensional, whole‐mounted radical prostatectomy (3D‐WMRP) specimens were generated and used as gold standard to determine tumor morphometric data. Between‐sample rates of upgrade and downgrade (highest GS and a novel cumulative GS) and upstage and downstage (laterality) were determined. Lesions ≥ 0.5 cm 3 or GS ≥ 7 were considered clinically significant. RESULTS: From 64 separate 3D‐WMRP lesions, 25 had significant volume (mean 1.13 cm 3 ) and 39 were insignificant (mean 0.09 cm 3 ) ( P  < 0.0001); 18/64 lesions were missed by TPMB, but only one was clinically significant with GS‐8 (0.02 cm 3 ). When comparing the cumulative GS of TPMB versus RP, 72% (n = 18) had identical scores, 12% (n = 3) were upgraded, and only 16% (n = 4) were downgraded. Laterality of TPMB and RP was strongly correlated, 80% same laterality, 4% were up‐staged, and 16% down‐staged. CONCLUSIONS: Our clinical‐pathology correlation showed very high accuracy of TPMB with a 5‐mm grid template to detect clinically significant PCa lesions as compared with 3D‐WMRP, providing physicians and patients with a reliable assessment of grade and stage of disease and the opportunity to choose the most appropriate therapeutic options. Prostate 73: 778–787, 2013. © 2012 Wiley Periodicals, Inc.